An in silico approach to elucidate structure based functional evolution of oxacillinase. (October 2016) - Pal, Arijit; Tripathi, Anusri
Graphical abstract: Highlights: Loops flanking helix5 of OXA might regulate substrate specificity and catalysis. Evolutionary trade-off between substrate versatility/selectivity exists in OXA evolution. Ten consensus/conserved residues had been identified as critical for OXA function. Small molecule inhibitors could be designed to target above mentioned ten sites. Abstract: Bacterial Oxacillinases (OXAs), genetically being extremely diverse and highly versatile in hydrolyzing antibiotics of different classes, holds utmost significant clinical importance. Hence, to analyze functional evolution of this enzyme, plausible changes in drug profile, affinity and binding stability of different subclasses of OXA with their preferred drugs, viz. penicillin, ceftazidime, imipenem/meropenem were investigated. Maximum-Likelihood dendrogram was constructed and based on tree topology, the least and most divergent variants of each clade were selected. Pocket characterization, enzyme structural stability and mutational effect were analyzed in silico . Modes of interaction of selected OXA variants with respective antibiotics were analyzed by Autodock4.0 and LIGPLOT. Comparative mobility profiling and subsequent ΔG° and Km calculations of representative OXA variants revealed that after RSBL evolution, perhaps, two competitive strategies evolved among the OXA variants. Either loops flanking helix5 gets stabilized or it becomes more flexible. Therefore, while OXA variants (e.g. OXA-2, OXA-32, OXA-23, OXA-133, OXA-24, OXA-25, OXA-51 and OXA-75) with highly stabilized loops flanking helix5 exhibited improved binding stability and affinity towards carbapenems, especially meropenem, OXA variants (e.g. OXA-10, OXA-251, OXA-48 and OXA-247) possessing highly flexibile loops flanking helix5 revealed their catalytic proficiency towards ceftazidime. Moreover, LIGPLOT and PROMALS3D jointly identified ten consensuses/conserved residues, viz. P68, A69, F72, K73, W105, V120, W164, L169, K216 and G218 to be critical for drug hydrolysis. Hence, novel inhibitors could be designed to target these sites.